2011
DOI: 10.1074/jbc.m111.221184
|View full text |Cite
|
Sign up to set email alerts
|

Protein Interactions of Phosphatase and Tensin Homologue (PTEN) and Its Cancer-associated G20E Mutant Compared by Using Stable Isotope Labeling by Amino Acids in Cell Culture-based Parallel Affinity Purification

Abstract: The tumor suppressor PTEN (phosphatase and tensin homologue) negatively regulates the PI3K pathway through its lipid phosphatase activity and is one of the most commonly lost tumor suppressors in human cancers. Though the tumor suppressive function involves the lipid phosphatase-dependent and -independent activities of PTEN, the mechanism leading to the phosphatase-independent function of PTEN is understood poorly. Some PTEN mutants have lipid phosphatase activity but fail to suppress cell growth. Here, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 43 publications
0
66
0
Order By: Relevance
“…By contrast, neither overexpression nor knockdown of IQGAP3 in HeLa and A549 lung adenocarcinoma cell lines, respectively, alters Akt activation [48]. Interestingly, phosphatase and tensin homolog (PTEN), which terminates Akt signaling by dephosphorylating PtdInsP 3 [49], co-immunoprecipitates with IQGAP1 [55]. Although the function of this interaction has not been identified, it could serve as an additional point of regulation of Akt.…”
Section: Iqgap1 Modulates Cellular Signalingmentioning
confidence: 99%
“…By contrast, neither overexpression nor knockdown of IQGAP3 in HeLa and A549 lung adenocarcinoma cell lines, respectively, alters Akt activation [48]. Interestingly, phosphatase and tensin homolog (PTEN), which terminates Akt signaling by dephosphorylating PtdInsP 3 [49], co-immunoprecipitates with IQGAP1 [55]. Although the function of this interaction has not been identified, it could serve as an additional point of regulation of Akt.…”
Section: Iqgap1 Modulates Cellular Signalingmentioning
confidence: 99%
“…For example, a PTENG20E mutant has been reported in patients with endometrial carcinoma, and in vitro analyses confirmed that this mutation reduces phosphatase activity to ~20% of the activity of wild-type PTEN (53). IQGAP1 co-immunoprecipitates with Flag-tagged PTEN from U87MG human glioma cells and with endogenous PTEN from both HEK293T and LN229 cells (54). Interestingly, mass spectrometry analysis with stable isotope labelling by amino acids in cell culture (SILAC) yielded higher ratios of IQGAP1 with PTENG20E than with wild-type PTEN, implying that this mutant may have a higher propensity to interact with IQGAP1 (54).…”
Section: Iqgap1 Binding Partnersmentioning
confidence: 99%
“…IQGAP1 co-immunoprecipitates with Flag-tagged PTEN from U87MG human glioma cells and with endogenous PTEN from both HEK293T and LN229 cells (54). Interestingly, mass spectrometry analysis with stable isotope labelling by amino acids in cell culture (SILAC) yielded higher ratios of IQGAP1 with PTENG20E than with wild-type PTEN, implying that this mutant may have a higher propensity to interact with IQGAP1 (54). Further work is required to ascertain whether IQGAP1 binds PTEN directly and if the interaction has any effect on PTEN function.…”
Section: Iqgap1 Binding Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…To search for new mutant p53R273H-specific binding proteins, we undertook a comparative immunoprecipitation (IP) analysis using stable isotope labelling by amino acids in cell culture (SILAC) and mass spectrometry. SILAC has proved to be a powerful approach to distinguish adventitious from specific interactors, while retaining many weaker or transient binding partners [19][20][21][22][23][24][25]. Through this method we discovered several new mutant p53-specific binding proteins.…”
Section: Introductionmentioning
confidence: 99%